Acceptance and Commitment Therapy (Act) in Psychotic Patient - Khairunnisa; Suksmi Yitnamurti (Faculty of Medicine, Universitas Airlangga, 2024)
Introductions: Psychosis is a condition of severe mental disorder characterised by the presence of disability in assessing reality. Schizophrenia is the most common psychotic disorder. It is also associated with long-term disability. ACT is one of the newest psychological interventions for psychotic patients. This paper aims to describe ACT as the newest psychotherapy intervention and its advantages for psychotic patients. Review: The management of psychosis is a combination of the use of antipsychotics, psychotherapy, and psychosocial therapy. ACT is one of the newest psychological interventions for psychotic patients that aims to increase the patient's psychological flexibility through six core processes of therapy: acceptance, cognitive defusion, being present, self as context, value, and committed action. ACT does not target symptom reduction. Therapists help patients recognise and reduce unnecessary struggles with psychological content so that patients can develop an accepting attitude and be able to move towards the values they hold. Conclusions: The use of third-wave behavioural therapy based on mindfulness and acceptance showed good results in patients with psychotic disorders. ACT aims to help individuals accept things that are beyond their control and commit to actions that can improve their lives. Research on the clinical adaptation of ACT for psychosis has shown good initial results in reducing distress due to psychotic symptoms, better regulation of emotions, and reducing relapsing rates.